Various novel insecticides are less toxic to humans, more specific to key pests - Elizabeth E Grafton-Cardwell; Larry D Godfrey; William E Chaney; Walter J Bentley (California Agriculture, 2005)
A number of novel insecticides have recently been registered for insect control in agriculture. A major advantage of these new products is that they act on insect biological processes that humans do not experience, such as molting. Many also have greater selectivity to target specific species, so they are less likely to harm natural enemies when compared with the broader spectrum organophosphate, carbamate, neonicotinoid and pyrethroid insecticides. Such novel insecticides currently in use include four targeting lepidopteran pests, three targeting sucking insects, one specific to dipteran leafminers and one insect growth regulator that controls a wide range of insects. One negative aspect of these insecticides is that because of their narrower range of activity — controlling only a limited number of pests — growers may need to apply additional pesticides for secondary pest groups that have poor biological control, increasing the total number of treatments per acre and total pest-control costs.